Case Study of Representation of the Rise of Social Criticism of the Police Through Google Veo 3 AI Videos - Muh. Sulaiman Dadiono (Academic Letters, 2025)
This article discusses the rise of artificial intelligence (AI) based video production through the Google Veo 3 platform that highlights and criticizes police performance. The purpose of this article is to analyze how AI videos are used as a medium for social criticism, the narratives they construct, and the public's response to the content. The results of the study show that AI videos are used as an alternative space for expression in voicing disappointment with the performance of the police, especially in issues of abuse of authority and corruption. Although the videos are fictional and artistic in style, their visual and narrative power has a significant impact on public perception. This article concludes that generative AI such as Google Veo 3 opens up space for the democratization of criticism, but also raises ethical and regulatory challenges in the digital ecosystem so that there must be additional regulatory recommendations related to this.